Formic acid production using a microbial electrolysis desalination and chemical-production cell. (November 2017) - Lu, Yaobin; Luo, Haiping; Yang, Kunpeng; Liu, Guangli; Zhang, Renduo; Li, Xiao; Ye, Bo
Graphical abstract: Highlights: The maximum current density in this study was much higher than previously reported. The electric consumption in the 72-MEDCC was 3.1–18.8% of those in the EDBMs. The mechanism of high performance in the 72-MEDCC was discussed. Abstract: The aim of this study was to investigate the feasibility and optimization of formic acid production in the microbial electrolysis desalination and chemical-production cell (MEDCC). The maximum current density in the MEDCC with 72 cm of the anode fiber length (72-MEDCC) reached 24.0 ± 2.0 A/m 2, which was much higher than previously reported. The maximum average formic acid production rate in the 72-MEDCC was 5.28 times higher than that in the MEDCC with 24 cm of the anode fiber length (37.00 ± 1.15 vs. 7.00 ± 0.25 mg/h). High performance in the 72-MEDCC was attributed to small membrane spacing (1 mm), high flow rate (1500 μL/min) on the membrane surface and high anode biomass. The minimum electricity consumption of 0.34 ± 0.04 kWh/kg in the 72-MEDCC was only 3.1–18.8% of those in the EDBMs. The MEDCC should be a promising technology for the formic acid production.